A Newborn Male Infant with Seizures, Cyanosis, Bradycardia, and Ischemic Stroke Due to Autosomal Dominant Hypocalcemia with a Missense Mutation in the CaSR Gene: A Case Report - Agdamag, Althea Samantha; Maclennan, Alexander; Brown, Brande M.; Ahmed, Anjum Mohyuddin; Parikh, Abhinav; Agdere, Levon; Ron, Nitin (International Journal of Innovative Research in Medical Science, 2023)
Autosomal dominant hypocalcemia is commonly caused by a gain-of-function mutation in the CaSR gene and inhibits calcium reabsorption in the kidneys by suppressing the secretion of parathyroid hormone. Laboratory findings typically result in hypocalcemia, hyperphosphatemia, hypomagnesemia, hypercalciuria, and low to normal parathyroid hormone. Clinically, patient presentation varies from asymptomatic to life-threatening. We present a full-term baby boy who exhibited episodic right lower extremity stiffening, cyanosis, and bradycardia at day of life 2 with confirmed seizure activity. The patient’s course was significant for poor feeding, right vocal cord paralysis, and an ischemic stroke in the posterior division of the right middle cerebral artery. Genetic work-up revealed the unique CaSR heterozygous missense variant mutation c2495T>C (p.lle832Thr), and STX16 gene variation. This patient’s sibling also carries the same mutation however is asymptomatic. It is important to monitor these patients for clinical manifestations, as gain-of-function mutations in the CaSR gene may carry complications such as nephrocalcinosis, changes in bone mineral density, and a predilection for epilepsy later in life.